PREVALENCE OF NEUROLOGICAL SINDROMES AND DISEASES OF THE NERVOUS SYSTEM - Babadjanova , Zamira (Medical science of Uzbekistan, 2023)
Diseases of the nervous system occur in 127.2 million, that is, in 25.8% of the European population, ranking second in the structure of mortality after coronary heart disease. According to the World Health Organization, "..there is a constant increase in the number of neurological diseases - cerebrovascular diseases, multiple sclerosis, epilepsy, diseases of the peripheral nervous system and Parkinson's disease." Of great importance is the relevance of many issues related to the optimization of medical care in primary health care, especially the provision of neurological care to the population by family doctors.